Agama Buddha: Analisis Bibliometrik pada Database Dimensions dalam Kurun Tahun 2018-2022 - Aldi Rizky Pratama (UIN Sunan Gunung Djati Bandung, 2023)
Indonesia is known as a multicultural country with six religions that are now officially recognized, one of which is Buddhism. Therefore, it is felt necessary to examine more deeply related to Buddhism in Indonesia, with the hope that one of the cultures in Indonesia will continue to be preserved. The purpose of this study is to analyze several published articles with the keyword Buddhism using bibliometric analysis techniques. With quantitative methods and bibliometric analysis, the authors try to display several tables containing several different categories. In the results and discussion, five categories were found, namely 1) Research Category for Research Field Purposes and Sustainable Development Goals, 2) Annual Development, 3) Most Active Researcher, 4) Most Affiliates, and 5) Most Productive Publishing Locations. The conclusion of this study is that there is still a lack of interest from researchers in Indonesia in researching the study of Buddhism. Even though in the category of affiliation and the most active publishing locations there are names from Indonesia, it still needs to be improved from the category of the most prolific writers.